ANALISIS POSITIONING TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO RITEL MODERN LAWSON DAN CIRCLE K - Destia Lovita Ananda; Kusumawati, Heni (Jurnal Akuntansi Dan Manajemen, 2025)
This research aims to determine whether there are differences in promotion, pricing, and location selection strategies affecting consumer purchasing decisions between the modern retail stores Lawson and Circle K in Yogyakarta. Simple random sampling was employed as the sampling method in this study, distributing questionnaires to consumers of Lawson and Circle K. The total number of respondents for this research was 120 for Lawson and 120 for Circle K. The analytical method utilized was the Mann-Whitney test. The analysis results indicate that (1) there is no difference in promotional strategies affecting consumer purchasing decisions between Lawson and Circle K; however, when examining individual indicators, one indicator supports the hypothesis, specifically in the direct marketing indicator, (2) there is no difference in pricing strategies affecting consumer purchasing decisions between Lawson and Circle K; nevertheless, when analyzing individual indicators, one indicator supports the hypothesis, particularly in the affordability indicator, (3) there is no difference in location selection strategies affecting consumer purchasing decisions between Lawson and Circle K; although, when examining individual indicators, one indicator supports the hypothesis, specifically in the transportation indicator.